The Competencies of Master Program Graduates: Employers’ Demands in Hospitality - K. V. Reshetnikova; M. D. Predvoditeleva (Управленческие науки, 2017)
Introduction, Purpose. This paper deals with one of the research questions arising in connection with the problem of Master degree students teaching who intend to work in the hospitality industry. The purpose of the article is to present results of research aimed at identifying the competencies required by the graduates of Master programs who start working in the Russian and international hotel industry organizations. Methods. The research methodology is based on the conceptual approaches to the study of competencies, developed by Russian and international researchers. In particular, this investigation capitalizes on the competency-based approach which was implemented during the course of the Bologna Process. The main data collection methods include analysis of documents (professional and educational standards) and in-depth interviews with experts (top and middle managers of hotels) with experience in the industry, complemented by questionnaires. Results. The result of the study is a list of graduates competencies of pre-experience Master programs that are in demand on the labor market in the hotel industry. The identified competencies are of interest primarily to the sphere of education. Discussion. The result can be employed for the development of educational standards, as well as curricula of educational Master programs in hospitality and syllabi of individual disciplines. In addition, the results of this study can be used by HR managers dealing with recruitment and selection of personnel for hospitality industry companies.